Discipline-specific competency-based curricula for leadership learning in medical specialty training: A critical review of the literature. Issue 2 (11th April 2018) - Turner, Sandra; Chan, Ming-Ka; McKimm, Judy; Dickson, Graham; Shaw, Timothy
Abstract : Purpose: Doctors play a central role in leading improvements to healthcare systems. Leadership knowledge and skills are not inherent, however, and need to be learned. General frameworks for medical leadership guide curriculum development in this area. Explicit discipline-linked competency sets and programmes provide context for learning and likely enhance specialty trainees' capability for leadership at all levels. The aim of this review was to summarise the scholarly literature available around medical specialty-specific competency-based curricula for leadership in the post-graduate training space. Design/methodology/approach: A systematic literature search method was applied using the Medline, EMBASE and ERIC (education) online databases. Documents were reviewed for a complete match to the research question. Partial matches to the study topic were noted for comparison. Findings: In this study, 39 articles were retrieved in full text for detailed examination, of which 32 did not comply with the full inclusion criteria. Seven articles defining discipline-linked competencies/curricula specific to medical leadership training were identified. These related to the areas of emergency medicine, general practice, maternal and child health, obstetrics and gynaecology, pathology, radiology and radiation oncology. Leadership interventions were critiqued in relation to key features of their design, development and content, with reference to modern leadership concepts. Practical implications: There is limited discipline-specific guidance for the learning and teaching of leadership within medical specialty training programmes. The competency sets identified through this review may aid the development of learning interventions and tools for other medical disciplines. Originality/value: The findings of this study provide a baseline for the further development, implementation and evaluation work required to embed leadership learning across all medical specialty training programmes.